Recent Developments in Highly Stereoselective Michael Addition Reactions Catalyzed by Metal Complexes - Reznikov, Alexander N.; Klimochkin, Yuri N. (Synthesis, 2020)
Achieving high enantioselectivity and diastereoselectivity simultaneously is a rather challenging task for asymmetric catalytic synthesis. Thanks to the rapid development of asymmetric transition-metal catalysis, significant progress has been made during recent years in achieving highly enantio- and diastereoselective conjugate addition reactions with a diverse combination of Michael donors and acceptors. This short review surveys the advances in transition-metal-catalyzed asymmetric diastereoselective Michael addition including diastereodivergent catalysis developed between 2015 and 2019. The review is divided into multiple parts according to the type of nucleophiles involved in the reaction.1 Introduction2 Addition of Functionalized Ketones and Dicarbonyl Compounds3 Addition of Aldimino Esters and Their Cyclic Analogues4 Addition of Indolin-2-ones5 Vinylogous Michael Reactions6 Other Michael Donors7 Cascade Reactions Initiated by Michael Addition8 Conclusion
Keywords: Michael addition; asymmetric catalysis; enantioselectivity; diastereoselectivity; transition-metal complexes